South European Part of Russia Land’s Degradation under the Influence of Dusty Storms - A. Ya. Glushko; V. V. Rasumov; M. D. Reikhany (Юг России: экология, развитие)
Dusty storms as the most dangerous meteorological phenomenon are widely practiced on the flat country of the south European part of Russia. Their negative influence are in mechanical restriction of top soil, the soil’s impoverishment, that is seen in its cadastral value. Dusty storms have negative influence at the agricultural potential of regions, inflict damage to the economy of South Russia.